Industry 4.0 and business process management - Tupa, Jiri; Steiner, Frantisek (2019)
Production companies are adopting new methods for the improvement of their managing production processes. The cost, quality and time are still key important attributes for process improvement. This is reason why the Business Process Management (BPM) is the core of management in different areas, e.g., quality management, sustainability management. The new technologies based on Internet of Things and Services, SMART solutions, and the concept Industry 4.0 are opening new possibilities of BPM implementation. This theoretical paper deals with a review of new trends in BPM and a presentation of the possibilities of core technologies for Industry 4.0 in phases of BPM applications.
Bibliografija: 21 jed.
Abstract.
Keywords: Industrija 4.0 -- Upravljanje procesima -- Učinkovitost -- Menadžment rizika